Personalized Medicine and Neurosurgery - Nicholas Theodore (Frontiers Research Topics, 2017)
The Precision Medicine Initiative, which was instituted by President Barack Obama on January 20, 2015, highlighted the importance that advances in genomics and related "-omic" approaches have made to science and medicine, and it set the stage for their federally funded and mandated integration into the delivery of health care. Whether these advances comprise large-scale approaches, such as The Cancer Genome Atlas, which provides a modern classification of cancers based on molecular profiles, or genealogy initiatives, which seek to trace the movement of our early ancestors out of Africa, genomic technology has taken us closer to developing targeted therapies and a refined understanding of our evolutionary journey. It is against this backdrop that we summarized some of the recent advances in the field of precision medicine, or personalized medicine, as they pertain to neurosurgery. In this e-Book collection provided by Frontiers in Surgery: Neurosurgery, we present a collection of articles by leaders in the field of neurosurgery that highlight domains using a personalized approach for the treatment of patients or avenues when personalization is possible and when it will likely alter the care of patients with neurological diseases.